Single Cell Protein—State-of-the-Art, Industrial Landscape and Patents 2001–2016 - Ritala, Anneli; Häkkinen, Suvi T.; Toivari, Mervi; Wiebe, Marilyn G. (Frontiers in Microbiology, 2017)
By 2050, the world would need to produce 1250 million tonnes of meat and dairy per year to meet global demand for animal-derived protein at current consumption levels. However, growing demand for protein will not be met sustainably by increasing meat and dairy production because of the low efficiency of converting feed to meat and dairy products. New solutions are needed. Single cell protein (SCP), i.e. protein produced in microbial and algal cells, is an option with potential. Much of the recent interest in SCP has focused on the valorisation of side streams by using microorganisms to improve their protein content, which can then be used in animal feed. There is also increased use of mixed populations, rather than pure strains in the production of SCP. In addition, the use of methane as a carbon source for SCP is reaching commercial scales and more protein-rich products are being derived from algae for both food and feed. The following review addresses the latest developments in SCP production from various organisms, giving an overview of commercial exploitation, a review of recent advances in the patent landscape (2001-2016) and a list of industrial players in the SCP field.